TRANSLATING ENGLISH TEXTS THROUGH AI: LIMITATIONS AND ADVANTAGES - Rakhimova Gavkhar Jamshid kizi, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract. This article examines the evolving role of Artificial Intelligence (AI) in the translation of English written texts, highlighting both its transformative potential and its inherent limitations. Rapid advances in neural machine translation (NMT) and natural language processing (NLP) have made AI tools faster, more accessible, and increasingly  accurate.  Nevertheless,  challenges  persist  in  cultural  interpretation, stylistic  adaptation,  and  data  security.  Through  a  comprehensive  analysis  of  the advantages and constraints of AI-assisted translation, this study argues that the most effective  approach  involves  a  collaborative  model  integrating  both  AI  and  human expertise.  The  findings  underline  the  need  for  continued  research  into  improving contextual  understanding,  ethical  use,  and  multilingual  inclusion  in  AI  translation technologies.